National Identity Strengthening Model Through Multicultural-Based Batik Development - Falla Rizqi Candra; Rosalia Indriyati Saptatiningsih (IJEDR: Indonesian Journal of Education and Development Research, 2023)
The research focuses on the National Identity Strengthening Model through Multicultural-Based Batik Development in Taman Village, Yogyakarta. Indonesia's diverse cultures, spanning various islands, lead to a multicultural society. Multiculturalism is key for harmonious coexistence and shaping the national identity. Batik, a national symbol, requires innovative motifs that incorporate cultural heritage from different regions. Conducted in Taman Village, Yogyakarta, the qualitative study involves thirteen participants: batik artisans, local residents, and batik users. Data is gathered via observation, interviews, and documentation, validated through source triangulation. Results highlight batik's development, blending diverse cultural elements into unique designs. These motifs showcase Indonesia's cultural richness, uniting traditional Yogyakarta patterns with those from different regions. This approach reinforces national identity. Positive feedback from locals and batik users demonstrates pride in promoting Indonesian culture and national identity through batik. Multicultural batik motifs effectively educate about Indonesia's heritage, particularly among the youth.